Demonstration of an abnormality of C apoprotein of very low density lipoprotein in patients with gout. Issue 6 (June 1985) - Macfarlane, D G; Midwinter, C A; Dieppe, P A; Bolton, C H; Hartog, M
Abstract : The very low density (VLDL) apolipoproteins of 12 male patients with gout have been studied by analytical isoelectric focusing. The relative percentage distribution of the C apolipoproteins was calculated and compared with that from 12 normolipidaemic and 12 'lipid-matched' controls. In the gout patients apolipoprotein CII (apo CII) represented 19.6% of the VLDL C proteins and the CII/CIII2 ratio was 0.57. In the normolipidaemic controls apo CII represented 28.8% and in the lipid-matched controls 33.1% of VLDL apo C, and the CII/CIII2 ratio approached one in each control group. These differences were significant. This suggests that a reduction in VLDL apo CII may predispose to the hypertriglyceridaemia that is commonly found in patients with gout.